PENGARUH CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP CORPORATE VALUE DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2020-2022) - Hilmansyah Hilmansyah; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2026)
For investors, in assessing the long-term prospects of a business entity, company value is a crucial indicator. Profitability and corporate governance are seen as key factors in increasing this value, while corporate social responsibility supports the relationship between variables. The analysis focused on 108 manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2022 period, considering that this sector has a strategic contribution to the national economy and demonstrates consistency in corporate governance and social responsibility reporting practices.      In this study, a quantitative approach was applied by conducting an analysis of public companies. Regression tests were used to examine the indirect and direct effects between variables. The results of the test show that there is a significant influence between corporate governance and the level of CSR disclosure, but corporate governance is positioned as a measure of the audit committee. Profitability, in further testing, has a positive effect on Corporate Value, while CSR disclosure and corporate governance do not have a positive effect in part. The Sobel method used for mediation testing shows that CSR disclosure is not yet capable of being an intervening variable in the relationship between profitability or corporate governance and Corporate Value.      These findings indicate that the market does not prioritize social responsibility and corporate governance in assessing corporate value. As a result, for investors, the effectiveness of CSR is still relatively limited.